2021
DOI: 10.1002/app.50730
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the residual monomer concentration of ε‐caprolactam in polyamide‐6 using thermogravimetric analysis coupled with Fourier transform infrared spectroscopy gas analysis

Abstract: For the anionic polymerization of ε‐caprolactam to polyamide‐6 the residual monomer concentration in the final polymer is an important characteristic. To determine this residual ε‐caprolactam monomer concentration, a fast and fail‐safe method was developed, which couples thermogravimetric analysis (TGA) with Fourier transform infrared spectroscopy (FTIR) gas analysis. FTIR allows an identification of the types of gasses released during heat treatment. Calibration of the infrared absorbance of ε‐caprolactam and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Without a catalyst, only minuscule amounts of caprolactam are obtained (Table 1, entry 6), along with trace impurities assignable to ɛ-caprolactam cyclic oligomers, [29] which are common impurities in the industrial polymerization process. [30] These oligomers can be extracted from the Nylon-6 starting material and observed by 1H NMR in CDCl 3 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Without a catalyst, only minuscule amounts of caprolactam are obtained (Table 1, entry 6), along with trace impurities assignable to ɛ-caprolactam cyclic oligomers, [29] which are common impurities in the industrial polymerization process. [30] These oligomers can be extracted from the Nylon-6 starting material and observed by 1H NMR in CDCl 3 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, little attention has been paid to the issue of time here, as they usually take a whole day. [17][18][19]27,36 It can be observed from Table S1 that solvent extraction for 2 h followed by vacuum drying 4 h was sufficient to remove residues from the polymerization product. This will provide important reference for the relevant research and production in the future.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…This is due to the fact that the drying of samples and corresponding escape of most of the water, which is also observed in previous literature. 25,27 Both PA6 polymer and CL monomer are easy to absorb water, especially the latter. That is to say, the higher mass percentage of CL in polymerization product, the higher water content of the sample.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…TG curves of UC13-DESs displayed a lesser weight loss than CPL, which is attributed to the formation of the hydrogen bond of CPL and UR (Figure S2). 39,40 The TG and DTG curves (Figure 1c) of UC13-FA-DESs under different FA ratios confirmed that the final decomposition temperatures T n of the substance gradually increase, which are 216.6 °C (UC13-FA1.9), 217.0 °C (UC13-FA2.4), 222.1 °C (UC13-FA3.2), and 224.0 °C (UC13-FA4.8), with the increase in the proportion of FA. The results testified to the fact that UC13-FA2.4-DESs with moderate FA content are beneficial to maintain the stable properties of DESs.…”
Section: Characteristic Properties Of the As-prepared Dessmentioning
confidence: 99%